2016
DOI: 10.1017/s1368980016000483
|View full text |Cite
|
Sign up to set email alerts
|

Colour correct: the interactive effects of food label nutrition colouring schemes and food category healthiness on health perceptions

Abstract: Objective: The purpose of the present study was to examine the effects of food label nutrition colouring schemes in interaction with food category healthiness on consumers' perceptions of food healthiness. Three streams of colour theory (colour attention, colour association and colour approach-avoidance) in interaction with heuristic processing theory provide consonant predictions and explanations for the underlying psychological processes. Design: A 2 (food category healthiness: healthy v. unhealthy) × 3 (foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…However, conflicting valences/coding and colours can undermine the understanding of the information and weaken the impact on purchase intention or purchase decisions, so they perform worse than directive systems such as warning labels and summary scores. 30 31 32 33 34 35 36 37 …”
Section: What Are the Different Types Of Fopl?mentioning
confidence: 99%
“…However, conflicting valences/coding and colours can undermine the understanding of the information and weaken the impact on purchase intention or purchase decisions, so they perform worse than directive systems such as warning labels and summary scores. 30 31 32 33 34 35 36 37 …”
Section: What Are the Different Types Of Fopl?mentioning
confidence: 99%
“…Understanding and correctly interpreting the nutrition information is another prerequisite, as highlighted by other papers in this issue. For example, Nyilasy et al (3) show that colour coding of information on the nutrition facts panel may even lead to adverse effects as the overall perception of a category as more v. less healthful can bias healthfulness evaluations of individual products, up to a point where healthy products are perceived as less healthy when the nutrition facts panel is colour-coded. Brand et al (4) demonstrate in a series of studies that other information presented on food packaging (i.e.…”
Section: Understanding and Interpretationmentioning
confidence: 99%
“…The traffic light is a type of color-coded FOP label that incorporates color schemes to indicate high (red), medium (orange), or low (green) saturated fat, sugar, and sodium content (and sometimes total fat). Nyilasy et al (2016) found that color-coded nutrition information reduced consumer perception of the healthiness of foods. However, in some studies, this type of label increased consumer ability to find healthier food options and attention to food labels ( Campos et al, 2011 ; Kelly et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of nutrition indicating icons and schemes has fueled the search for developing simple, standardized, and science-based criteria for communicating food products' nutritional content and relative healthfulness ( Smith et al, 2014 ; Bialkova and Trijp, 2010 ). Comprehension of these food labels is vital in communicating a healthy and nutritious diet and helps consumers recover from chronic illnesses like heart failure and other diseases, including obesity ( Nyilasy et al, 2016 ). The Nutrition Facts Panel (NFP) display provides consumers with more detailed nutrient-specific information than the FOP.…”
Section: Introductionmentioning
confidence: 99%